1997
DOI: 10.1152/ajprenal.1997.273.5.f777
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and renal hemodynamic changes in the luteal phase of the menstrual cycle mimic early pregnancy

Abstract: Blood pressure decreases during early pregnancy in association with a decrease in peripheral vascular resistance and increases in renal plasma flow and glomerular filtration rate. These early changes suggest a potential association with corpora lutea function. To determine whether peripheral vasodilation occurs following ovulation, we studied 16 healthy women in the midfollicular and midluteal phases of the menstrual cycle. A significant decrease in mean arterial pressure in the midluteal phase of the cycle (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
133
4
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(149 citation statements)
references
References 30 publications
9
133
4
1
Order By: Relevance
“…As a result, there are increased circulating concentrations of these hormones in women (Chapman et al 1997;Chidambaram et al 2002;Szmuilowicz et al 2006). In addition, it has been doi: 10.17221/32/2016-CJAS demonstrated that plasma REN, ANG, and ALD concentrations differ between the different phases of the estrous or the menstrual cycle (Szmuilowicz et al 2006).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, there are increased circulating concentrations of these hormones in women (Chapman et al 1997;Chidambaram et al 2002;Szmuilowicz et al 2006). In addition, it has been doi: 10.17221/32/2016-CJAS demonstrated that plasma REN, ANG, and ALD concentrations differ between the different phases of the estrous or the menstrual cycle (Szmuilowicz et al 2006).…”
mentioning
confidence: 99%
“…In normotensive women, elevated concentrations of REN and ALD have been described in the luteal phase of the menstrual cycle compared with the follicular phase (Sealey et al 1994;Chapman et al 1997;Chidambaram et al 2002). However, a proportional increase in ANG concentration was not found.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Observational studies have demonstrated that BP is lower when E 2 levels peak during the luteal phase than when they are at their nadir during the follicular phase of the menstrual cycle (Dunne et al, 1991;Karpanou et al, 1993;Chapman et al, 1997). Menopause is associated with a significant increase in BP in cross-sectional studies (Staessen et al, 1998).…”
Section: Estrogen Receptorsmentioning
confidence: 99%